2019
DOI: 10.1055/s-0039-3400454
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes following Arthroscopic Triangular Fibrocartilage Complex Repair

Abstract: Background Triangular fibrocartilage complex (TFCC) injury is a common cause of ulnar-sided wrist pain, which may lead to serious physical impairments. Arthroscopic repair has benefits such as less soft tissue damage, greater surgical accuracy, and may lead to faster recovery than open repair. Objective The purpose of this study was to determine the functional outcome of patients with symptomatic TFCC injuries treated with arthroscopic debridement or repair. Patients and Methods A retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 21 publications
1
13
0
6
Order By: Relevance
“…In comparison with the current literature on adult cases, the presented results in children and adolescents may be considered similar overall [43][44][45]. However, as in the analyzed adolescent cohort, many different techniques and approaches have been reported in adults so far.…”
Section: Discussionsupporting
confidence: 71%
“…In comparison with the current literature on adult cases, the presented results in children and adolescents may be considered similar overall [43][44][45]. However, as in the analyzed adolescent cohort, many different techniques and approaches have been reported in adults so far.…”
Section: Discussionsupporting
confidence: 71%
“…Most of the data presented are referred to atraumatic septic arthritis with 2–5 infections per 100,000 in the general population and up to 38 per 100,000 individuals with rheumatoid arthritis [ 62 ]. The infection rate after arthroscopy can only be estimated from case series and is reported to be between 0 and 0.6% [ 8 , 36 , 67 , 68 , 83 ]. One study investigating the complications after wrist arthroscopy of 10,107 patients reported an incidence rate of 0.04% [ 45 ].…”
Section: Epidemiology and Pathophysiologymentioning
confidence: 99%
“…When comparing studies it is important to know the characteristics of the populations investigated; acute or delayed repair, concomitant injuries, type of tear and type of repair used. Other studies on TFCC repair have shown PRWE scores of between 5 and 19.5 (Selles, d'Ailly et al 2020, Thalhammer, Haider et al 2021, where better results were achieved in a population with very strict exclusion criteria and with no reoperations (Thalhammer, Haider et al 2021). After trauma, duration of symptoms before surgery probably has an impact on outcome.…”
Section: Discussionmentioning
confidence: 96%